2001
DOI: 10.1080/12795119.2001.9692337
|View full text |Cite
|
Sign up to set email alerts
|

Efforts sur une conduite sous-marine en zone côtière

Abstract: Nous avons mesuré les efforts exercés sur un cylindre horizontal près du fond par l'action de la houle se propageant vers la côte. Celle-ci est modélisée par une plage de pente constante qui va induire une déformation progressive de la houle. Les efforts mesurés sont influencés par la hauteur et la dissymétrie de la houle ainsi que par l'écartement du cylindre par rapport au fond. Une modélisation de l'effort en ligne par la formulation de Morison est également menée et les coefficients hydrodynamiques corresp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 6 publications
1
5
0
Order By: Relevance
“…Comparing the values of C D , the authors observed an overall good agreement with the non-linear fit carried out by Bryndum et al [14] and a slight underestimation of the present experiments as compared to those performed by Sarpkaya and Rajabi [12], Neill and Hinwood [15], and Chevalier et al [16], even if few values of C D are present in the above works. With regard to C MH , Figure 9b shows the comparison between the current dataset and the values obtained by Sarpkaya and Rajabi [12], Bryndum et al [14], Neill and Hinwood [15], Chevalier et al [16], and Aristodemo et al [19]. The present values of C MH are lower than those calculated by Sarpkaya and Rajabi [12], Bryndum et al [14] and, in particular, by Aristodemo et al [19], while they are slightly higher than those obtained by Neill and Hinwood [15] and Chevalier et al [16].…”
Section: Calibration Of Semi-empirical Formulassupporting
confidence: 89%
See 3 more Smart Citations
“…Comparing the values of C D , the authors observed an overall good agreement with the non-linear fit carried out by Bryndum et al [14] and a slight underestimation of the present experiments as compared to those performed by Sarpkaya and Rajabi [12], Neill and Hinwood [15], and Chevalier et al [16], even if few values of C D are present in the above works. With regard to C MH , Figure 9b shows the comparison between the current dataset and the values obtained by Sarpkaya and Rajabi [12], Bryndum et al [14], Neill and Hinwood [15], Chevalier et al [16], and Aristodemo et al [19]. The present values of C MH are lower than those calculated by Sarpkaya and Rajabi [12], Bryndum et al [14] and, in particular, by Aristodemo et al [19], while they are slightly higher than those obtained by Neill and Hinwood [15] and Chevalier et al [16].…”
Section: Calibration Of Semi-empirical Formulassupporting
confidence: 89%
“…A more scattered range for KC compared to A/d can be observed since the Keulegan-Carpenter number depends on the apparent wave period which suffers from small oscillations near the free surface due to the appearance of spurious trailing waves. Figure 9a shows the present values of C D as a function of KC plotted against the experiments conducted by Sarpkaya and Rajabi [12], and Bryndum et al [14] through a non-linear fit of the laboratory data (Neill and Hinwood [15] and Chevalier et al [16]). Comparing the values of C D , the authors observed an overall good agreement with the non-linear fit carried out by Bryndum et al [14] and a slight underestimation of the present experiments as compared to those performed by Sarpkaya and Rajabi [12], Neill and Hinwood [15], and Chevalier et al [16], even if few values of C D are present in the above works.…”
Section: Calibration Of Semi-empirical Formulasmentioning
confidence: 99%
See 2 more Smart Citations
“…For bottom-mounted submarine pipelines, values of Morison hydrodynamic coefficients have been evaluated for different wave and current conditions based on field investigations (Grace and Zee, 1981;Lambrakos et al, 1987) and small and large scale laboratory experiments (Sarpkaya and Rajabi, 1980;Norwegian Hydrodynamic Laboratories, 1985;Cheong et al, 1987;Veritas Offshore Technology, 1988;Bryndum et al, 1983Bryndum et al, , 1992Benassai, 1993;Neill and Hinwood, 1998;Chevalier et al, 2000;Tomasicchio et al, 2007). Some authors (Sarpkaya, 1981;Bearman et al, 1984;Sarpkaya and Wilson, 1984;Chaplin and Subbiah, 1997;Sarpkaya, 2001) proposed, for limited KC and Re ranges, additional terms in the basic Morison equations in order to minimize the differences between the experimental and the simulated forces.…”
Section: Introductionmentioning
confidence: 99%